Paracyclophane‐based Silver Phosphates as Catalysts for Enantioselective Cycloisomerization/Addition Reactions: Synthesis of Bicyclic Furans. Issue 17 (11th July 2018) - Force, Guillaume; Ki, Yvette Lock Toy; Isaac, Kévin; Retailleau, Pascal; Marinetti, Angela; Betzer, Jean‐François
Abstract: This manuscript discloses the first use of chiral phosphates based on C2‐symmetric paracyclophane scaffolds as chiral counterions in transition metal catalysis, showing that they may compare favorably with other known chiral phosphates, such as the TRIP phosphate. The targeted catalytic reaction is a silver(I) promoted domino heterocyclization of 2‐(1‐alkynyl)‐2‐alken‐1‐one derivatives, in the presence of C ‐, or N ‐nucleophiles, which provides an efficient access to substituted bicyclic furans. Results show that high levels of enantioselectivity can be attained with either paracyclophane‐based phosphates or TRIP phosphates, when the nucleophilic reactants display N‐H functions in appropriate positions, near to the nucleophilic center. Therefore, the involvement of H‐bonding between the NH function and the phosphate in the enantiodetermining step is postulated. Abstract :